PLA PLASTICIZED WITH ESTERS FOR PACKAGING APPLICATIONS - BONDAREV, Andreea; CUC, Stanca; BOMBOȘ, Daniel; PERHAIȚĂ, Ioana; BOMBOȘ, Dorin (Studia Universitatis Babeș-Bolyai Chemia, 2023)
In this study, polylactic acid PLA was melt blended with bis(2-(2-butoxyethoxy)ethyl) adipate, tributyl citrate and/or sorbitan monooleate. The thermo-mechanical analysis of plasticized PLA highlighted an improvement in its behavior. Thus, the plasticization of PLA with the tested esters favored the lowering of its vitrification temperature and the bending resistance of the tested materials at ss varied in an area of interest for all the tested plasticizers. No significant difference was noted between the maximum flexural strengths and the elongation at deformation recorded at 25°C and those at 4°C for the three recipes. Also, the weight loss of PLA recipes in contact with water decreases in the presence of hydrophobic plasticizers.